An Annotated Bibliography of Financial Therapy Research: 2010 to 2018 - Christina Glenn; Brandy Caulfield; Megan A McCoy; Jordan R. Curtis; Nathan Gale; Nathan Astle (Journal of Financial Therapy, 2019)
The purpose of this paper is to expand upon Mentzer, Britt, Samuelson, and Herrera’s (2010) annotated bibliography of research conducted in the field of financial therapy prior to 2010 and provide readers with a current overview of financial therapy research published since that time. Annotated bibliographies are categorized by topics and future research in each area is suggested. In addition, two tables were developed to provide readers a snapshot of the current landscape of financial therapy. The first table provides a list of journals of published articles featuring financial therapy or related topics. The second table provides an overview of types of research, population studies, key topics, as well as highlighting whether theory and financial therapy are overtly referred to within the article.
Keywords: financial therapy; financial coaching; financial planning; financial anxiety; financial stress; marriage and family therapy; social work; mental health professionals; couples and money; college students